Pengembangan Instrumen Penilaian Berbasis Karakteristik Penilaian Autentik Sebagai Alat Evaluasi Pada Materi Teks Eksposisi di Kelas X SMAN 1 Kota Jambi - Albertus Sinaga; Liza Septa Wilyanti; Priyanto , (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2017)
ABSTRACT The purpose of this study is to Research and Development research or research and development. This research produces an assessment instrument based on authentic assessment characteristics as an evaluation tool on exposition text material in grade X SMA N 1 Kota Jambi. Through this research, it is expected that the assessment instrument based on authentic assessment characteristic used as an evaluation tool on exposition text material in grade X SMA N 1 Kota Jambi becomes more qualified and effective in order to achieve the objectives of the learning itself. From the results of the current study, the assessment instrument used by teachers in Class X SMA N 1 Kota Jambi is in the category of eligibility and suitability of 60.00% (quite appropriate). Therefore, the analysis of the shortage of instruments to be further developed. The development of the instrument is carried out to improve the quality and effectiveness expected to increase the chances of achieving the maximum learning objectives. Keywords: assessment instrument, authentic assessment, exposition texts